The first component of human complement - Sim, R (1976)
1. Procedures for partial purification of C1 and Cī are described and methods for the isolation of subcomponents C1r and C1s from C1 and Cī preparations have been developed. 2.1. Structural studies of C1r derived from C1 and Cī have shown that C1r, like C1s, exists in serum as a proenzyme, which is activated by limited proteolysis. 2.2. C1r and C1s are both single polypeptide-chain zymogens of 83,000 molecular weight with similar amino acid compositions. They are distinct in carbohydrate composition and antigenic properties. Activation of C1r and C1s occurs without loss of glycopeptides but loss of small peptides may occur. 2.3. C1r̄ and C1s̄ bind one mole of DFP per mole of protein. The amino acid sequences of the first 20 residues of the 26,000 molecular weight diisopropylphosphate-binding polypeptide chains of C1r̄ and C1s̄ show a high degree of sequence identity with corresponding regions of serine proteases such as trypsin and plasmin. C1r̄ and C1s̄ are therefore identified as serine proteaces of similar size and structure to plasmin. The structure and mode of activation of C1r and C1s and other serine protease zymogens are compared. 3.1. The enzymic activities of C1r̄ and C1s̄ have been investigated. C1r̄ cleaves C1s but did not hydrolyse any synthetic substrate tested. C1s̄ cleaves C2 and C4 and hydrolyses several amino acid esters. The proteolytic specificities of C1r̄ and C1s̄ are discussed. 3.2. Rapid and convenient assays for C1r̄ and C1s̄, suitable for kinetic studies of zymogen activation, have been developed. 4.1. The interactions of C1q, in solution or bound to antibody-antigen complexes, with C1r and C1s have been examined. 4.2. In solution, C1r and C1s form strong Ca2+-dependent complexes containing 2C1r + 2C1s molecules, or 4C1r + 4C1s molecules. C1r, C1s and the C1r-C1s complexes interact weakly with C1q. 4.3. When C1q is bound to immune complexes, C1r and C1r-C1s complexes bind strongly to C1q. C1s does not bind to C1q in the absence of C1r 4.4. Activation of C1r and C1s does not appear to alter their binding affinity for other subcomponents either in solution or when bound to antibody-antigen. 5.1. Spontaneous activation of C1r and C1s in solution has been studied. C1s does not activate autocatalytically. Absolute stability of C1r preparations was not observed, but it is concluded that auto-activation of C1r does not contribute significantly to the instability of C1r. 5.2. When fixed to antibody-antigen-C1q complexes, C1r does not activate unless C1s is also present. The effect of C1s on C1r activation does not require C1s̄ enzymic activity and it is apparent that C1s fulfills a binding requirement. 5.3. The mechanism of activation of C1 on interaction with immune complexes is discussed.